Multidrug resistance in enteric pathogens from smallholder poultry farms in peri-urban Dhaka: One Health implications - K. B. M. Saiful Islam; Syeeda Shiraj-Um-Mahmuda; Md. Roknuzzaman Khan; Md. Khairul Islam; Md. Akib Zabed; Afroj Zahan; Syeeda Shiraj-Um-Monira; Faisol Talukdar (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2026)
Background Antimicrobial resistance (AMR) in food animal pathogens poses a growing public health threat, particularly in low-resource settings where zoonotic transmission is poorly monitored. Objective This study investigated the occurrence, spatial distribution, and AMR profiles of enteric pathogens isolated from chickens reared in smallholder commercial poultry farms in Bangladesh. Methods Cecal samples (n=100) were collected from broiler and layer chickens across ten peri-urban locations within 50 km radius of Dhaka city. Bacterial isolation and identification were performed according to standard protocols. Antibiotic susceptibility was assessed using disk diffusion against 12 commonly used antibiotics. The multiple antibiotic resistance (MAR) index and prevalence of multidrug resistant (MDR) were calculated. Statistical analyses included chi-square tests, analysis of variance (ANOVA), and t-tests. Results A total of 270 bacterial isolates were recovered, predominantly Escherichia coli (55.9%) and Salmonella spp. (16.7%). Resistance was highest to Amoxicillin (93.3%), Streptomycin (52.6%), and Tetracycline (46.3%), while Ceftriaxone showed the lowest resistance (6.7%). Overall, 71.5% of isolates were multidrug-resistant with broiler-derived strains showing significantly higher MDR prevalence (78.8%) and MAR index (0.41 ± 0.11) than layer-derived strains (62.2%, 0.30 ± 0.09; p<0.001). Spatial analysis revealed significant variation in isolate counts and resistance burden across locations, with Narsingdi, Savar, and Araihajar identified as high-risk zones (p<0.05). Conclusion The high prevalence of MDR enteric pathogens and elevated MAR indices in broiler farms highlight the zoonotic risk posed by poultry feces. These findings emphasize the need for targeted antimicrobial stewardship and surveillance within the One Health framework.